RESEACHING THE ASPECTS OF INTERACTION BETWEEN EDUCATORS AND STUDENTS IN THE DISTANCE LEARNING SYSTEM - Rosinska, Olena; Horbenko, Halyna; Zhuravska, Oksana (Journal of Information Technologies in Education (ITE), 2021)
Practical experience of distance learning in Institute of Journalism of Borys Grinchenko Kyiv University proves productivity of combining full-time and distance learning forms on the Moodle platform. The purpose of the research is to study how the Institute students and educators assess difficulties and achievements of distance learning, to analyze the differences and coincidences between the inquiries from students and educators, to establish Moodle-added platforms, suitable for all education process participants. The research studies the inquiries of students and educators in Institute of Journalism of Borys Grinchenko Kyiv University due to the change of an activity format during COVID-19 quarantine measures. 62 professors, 302 bachelors and masters have been inquired, as well as the participants’ activity of internal distance learning system and the level of technical possibilities of access to it, utilization rate of platforms and services have been under analysis to receive the data. 1/3 of the respondents consider distance learning to be a critical need of that period, and more than 2/3 admit that it as a perspective learning form. 40% of educators regularly use distant technologies in their work and believe that the main problem is absence of face-to-face communication with students. More than 90% of students have an easy access to distance learning; moreover, poor Internet connection was specified as a problem for its implementation. Up to 70% of respondents consider the use of different learning platforms to be productive, a significant amount of them are video conference services. The monitoring provides grounds for further study of psychological needs for face-to-face communication, since the data received from the respondents demonstrate different approaches to this issue.